A review on durability of basalt fiber reinforced concrete - Li, Yan; Zhang, Jiupeng; He, Yinzhang; Huang, Guojing; Li, Junbo; Niu, Zhenxing; Gao, Bo (Composites science and technology, 2022)
In order to further broaden the application scope of basalt fiber reinforced concrete (BFRC), prolong service life in complex environment, master development status and sort out development needs, the durability of BFRC in complex environment was systematically summarized. First of all, the reason and damage mechanism of concrete deterioration in a variety of harsh environment are analyzed and grasped. Secondly, the strengthening mechanism of basalt fiber (BF) structure in permeability, carbonization, sulfate erosion, alkali environment, freeze-thaw cycle and high temperature is reviewed in detail, and the strengthening effect and performance of BFRC are discussed from the perspective of macroscopic properties and microscopic pore structure. The addition of BF reduces the generation and development of early microcracks in concrete structures, promotes the densification of structures on a microscopic scale. What's more, the permeability, carbonation resistance, acid and alkali corrosion resistance, frost resistance and high temperature resistance of concrete structures can be significantly improved. Finally, the problems in the current research are summarized and research ideas to cope with the environmental complexity are proposed to provide a research basis for BFRC to maintain excellent performance in the actual complex application scenarios. This paper focuses on the strengthening effect of basalt fiber on cement-based materials, and mainly introduces its strengthening effect and action mechanism from several aspects in the figure. [Display omitted]